Nonenzymatic glycosylation of isolated human immunoglobulin‐G by D‐ribose. (16th June 2022) - Ahmad, Saheem; Al‐Shaghdali, Khalid; Rehman, Shahnawaz; Khan, Mohd. Yasir; Rafi, Zeeshan; Faisal, Mohammad; Alatar, Abdulrahman A.; Tahir, Iram Khan; Khan, Saif; Ahmad, Shafeeque; Shahab, Uzma
Abstract: Glycation is vital in terms of its damaging effect on macromolecules resulting in the formation of end products, which are highly reactive and cross‐linked irreversible structures, known as advanced glycation end products (AGEs). The continuous accumulation of AGEs is associated with severe diabetes and its associated ailments. Saccharides with their reducing ends can glycate amino acid side chains of proteins, among them glucose is well‐known for its potent glycating capability. However, other reducing sugars can be more reactive glycating agents than glucose. The D‐ribose is a pentose sugar‐containing an active aldehyde group in its open form and is responsible for affecting the biological processes of the cellular system. D‐ribose, a key component of many biological molecules, is more reactive than most reducing sugars. Protein glycation by reducing monosaccharides such as D‐ribose promotes the accelerated formation of AGEs that could lead to cellular impairments and dysfunctions. Also, under a physiological cellular state, the bioavailability rate of D‐ribose is much higher than that of glucose in diabetes, which makes this species much more active in protein glycation as compared with D‐glucose. Due to the abnormal level of D‐ribose in the biological system, the glycation of proteins with D‐ribose needs to be analyzed and addressed carefully. In the present study, human immunoglobulin G (IgG) was isolated and purified via affinity column chromatography. D‐ribose at 10 and 100 mM concentrations was used as glycating agent, for 1–12 days of incubation at 37°C. The postglycation changes in IgG molecule were characterized by UV‐visible and fluorescence spectroscopy, nitroblue tetrazolium assay, and various other physicochemical analyses for the confirmation of D‐ribose mediated IgG glycation. Significance statement: 1. D‐ribose‐induced glycation leads to structural perturbations in immunoglobulin G (IgG), the formation of IgG‐advanced glycation end products, and the generation of oxidative stress. 2. UV‐visible spectroscopy revealed the hyperchromicity of glycated IgG increases with the increase in the concentration of D‐ribose and time interval. 3. The early glycation products that is, Amadori products or ketoamines formed during D‐ribose mediated glycation of IgG were assessed by nitroblue tetrazolium assay and found to be increased initially in the first 5 days. 4. Hydroxymethylfurfural, carbonyl content, thiobarbituric acid reactive substances, and fluorescence intensity were found to be increased in glycated IgG as compared to the native analog. 5. Free lysine and arginine were found to be decreased in glycated IgG in comparison to the native conformer of the protein.